Examining the effect of prenatal testosterone and aggression on sporting choice and sporting longevity. (1st October 2017) - Reed, Scott; Meggs, Jennifer
Abstract: Digit ratio (2D:4D; a putative correlate of prenatal testosterone) has been reported to be negatively associated with aggression in non-sporting and sporting populations. 2D:4D has previously been suggested to be a potential biomarker for successful competitive performance within football, rugby, athletics, skiing, and gym-based exercises. However, to date no study has attempted to investigate prenatal testosterone levels as a predictor of sporting choice. This study included a sample of both athletes and non-sports people in order to examine associations between prenatal testosterone (2D:4D), aggression, choice of sport (contact vs. non-contact), attainment level, and longevity. 200 male participants completed a self-report measure for aggression followed by providing a hand scan, which was later used to measure 2D:4D using Vernier Calipers. Results showed individuals involved in sport exhibited significantly greater levels of both prenatal testosterone (lower 2D:4D) and physical aggression compared with their non-sporting counterparts. Athletes from contact sports (rugby and football) were found to have significantly lower 2D:4D and significantly higher levels of physical aggression compared to athletes from non-contact sports (basketball, golf, weight-training, badminton). Additional findings, regarding longevity, showed those exposed to higher levels of prenatal testosterone (low 2D:4D) had been involved in sport for more years compared to those with high 2D:4D, adjusting for age. Findings may contribute to more reliable predictions of sporting selection and longevity. Future studies should look to replicate findings across a greater variety of sports using professional/elite populations. Highlights: 2D:4D ratio has been negatively associated with aggression. This study included a sample of contact and non-contact athletes and non-sports people. Sports people have lower 2D:4D and higher physical aggression than non-sport people. Contact sport athletes have significantly lower 2D:4D than non-contact sports people. Findings could be replicated in different sports and contexts.